คุณสมบัติของ “หญิงดี” ใน สุภาษิตสอนหญิงภาคใต้ที่สัมพันธ์กับความคิดความเชื่อทางพระพุทธศาสนา THE QUALIFICATIONS OF “WELL-BEHAVED WOMEN” IN SUPASIT SORN YING OF THE SOUTHERN RELATED TO BUDDHIST NOTIONS AND BELIEFS - จีนนุ่น, พัชลินจ์ (วารสารศรีนครินทรวิโรฒวิจัยและพัฒนา สาขามนุษยศาสตร์และสังคมศาสตร์, 2017)
บทคัดย่อ บทความนี้มีจุดมุ่งหมายเพื่อศึกษาคุณสมบัติของ “หญิงดี” ใน สุภาษิตสอนหญิงภาคใต้ที่สัมพันธ์กับความคิดความเชื่อทางพระพุทธศาสนา โดยศึกษาจากเรื่องสุภาษิตสอนหญิงคำกาพย์ สุภาษิตคำกาพย์ ฉบับศูนย์วัฒนธรรม มหาวิทยาลัยราชภัฏภูเก็ต หมายเลข 291 สุภาษิตสอนหญิง ฉบับนางนิล ทวีเศษ และสุภาษิตสอนหญิง ฉบับศูนย์วัฒนธรรม มหาวิทยาลัยราชภัฏนครศรีธรรมราช ผลการศึกษาพบว่าผู้แต่งสุภาษิตสอนหญิงทั้งสี่สำนวนต่างก็กำหนดคุณสมบัติของ “หญิงดี” ที่สัมพันธ์กับความคิดความเชื่อในพระพุทธศาสนา ดังนี้ คุณสมบัติทางกาย คือ “หญิงดี” ต้องมีกายที่สำรวมทั้งในขณะเดิน นั่ง หัวเราะ กิน นอน การแสดงสีหน้า แววตา และการทำกิจกรรมต่างๆ คุณสมบัติทางวาจา คือ “หญิงดี” ต้องมีวาจาที่ไพเราะอ่อนหวาน รู้จักพูด ถาม และสนทนากับผู้อื่น คุณสมบัติทางใจ คือ “หญิงดี” ต้องรู้จักระงับโทสะ มีความเพียรพยายาม ใจบุญสุนทาน ละโลภโกรธหลง เห็นความไม่เที่ยงของสรรพสิ่ง และรู้จักใช้ปัญญา นอกจากนี้ ยังต้องมีคุณสมบัติด้านการปฏิสัมพันธ์กับเพื่อนมนุษย์ด้วยกัน คุณสมบัติด้านพฤติกรรมที่แสดงออกสัมพันธ์กับความคิดความเชื่อในพระพุทธศาสนาตั้งแต่ระดับศีล สมาธิและปัญญา ทั้งนี้ผู้แต่งน่าจะมีนัยแฝงเพื่อฝึกฝนหญิงชาวใต้ที่ “สมบูรณ์แบบ” ตามหลักพระพุทธศาสนาเพื่อให้ดำเนินชีวิตอย่างสงบสุขและไปเกิดในภพภูมิที่ดี ทั้งอาจเป็นการสร้างพลังอำนาจแฝงของผู้หญิงอันจะยังประโยชน์ต่อสังคม และเป็นการจัดระเบียบผู้หญิงภาคใต้สมัยโบราณในเชิงลึกเพื่อมิให้ส่งผลกระทบต่อการปกครองท้องถิ่น Abstract This article aims at examining the qualifications of “well-behaved women” in SUPASIT SORN YING of the Southern related to Buddhist Notions and Beliefs in SUPASIT SORN YING KAM KAAP (A type of Thai verse) SUPASIT KAM KAAP number 291, which belongs to Phuket Rajabhat University’s cultural centre, SUPASIT SORN YING which belongs to Mrs. Nil Thaweeset and SUPASIT SORN YING which belongs to Naknonsithammarat Rajabhat University’s cultural centre. It was found that the qualifications of “well-behaved women” were closely related to the Buddhist notions and beliefs. Those qualifications included with having good physical manners: being clam when walking, sitting, laughing, eating, sleeping, expressing their emotions through their faces and eyes as well as doing other activities. Regarding to speech qualifications, “well-behaved women” were required to express sweet and beautiful speeches, knowing when and how to deliver them properly. In connection with spiritual qualifications, “well-behaved women” must be capable of restraining anger, pursuing endeavors, being charitable, controlling their greed and obsessions, perceiving uncertainty of all things and knowing how to apply their wisdom. Besides, the aspect of interpersonal interaction with others was also noted. It was also found that the mentioned qualifications were pertained to Buddhist notions and beliefs in all three levels: morality (sila), concentration (Samadhi) and wisdom (panna). Here, the authors’ intentions were probably to train the southern women to be “perfect” in following the Buddhist principles. By following those principles, they could live happily and peacefully in the society and would be able to sustain such happiness and peace of minds in their next life as well. In addition, it could be woman’s implicit power formation which will benefit in the society and the promotion of the in-depth re organisation of women within the ancient southern region, avoiding impacts to local administration.